Food preferences in times of pandemic. The case of chilean older people - Troncoso-Pantoja, Claudia; Garrido-Ramírez , Carolina; Gatica-Quiroga, Camila Inés; Salas-Moyano, Cristina Javiera (Horizonte Sanitario, 2022)
Objective: The social isolation caused by COVID-19 has promoted changes in lifestyles, affecting the well-being of the elderly. Therefore, the objective of the study is to interpret the influence of emotional and socioeconomic factors in food preferences of older people of the Gran Concepcion, Chile, in times of pandemic.Materials and methods: For the achievement of its purposes, an investigation was carried out that responds to the qualitative paradigm with the interpretive phenomenological approach of Heidegger. Participants were selected by intentional sampling based on the selection criteria and considering the sample size resulting from the saturation point. The study included a total of 12 elderly, who were interviewed virtually; the resulting data was coded, regrouped and analyzed using a content analysis technique.Results: The favorite dishes respond to those of the local culture; on the other hand, emotional and economic aspects are not recognized in the selection of food and food preferences. The communication achieved using social networks with their families is identified as positive and does not influence their eating behaviors.Conclusions: For this group of older people, the experience of social isolation due to COVID-19 was not enough to modify food preferences.Keywords: Aged; food preferences; social isolation; qualitative research.